FOREST FIRES AS A HUMAN RIGHTS VIOLATION: THE STATE'S ROLE IN PROTECTING THE RIGHT TO A HEALTHY ENVIRONMENT - yanti, saskia dwi (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2024)
The 1945 Constitution of the Republic of Indonesia guarantees the right to a good and healthy living environment, as stated in Article 28H paragraph (1). This places a responsibility on the state to ensure the fulfillment of these rights. This paper addresses the issue of forest fires, which violate the right to a healthy environment due to the harmful effects of smoke, mainly when caused by human actions. It examines how the law regulates forest fires and the state's responsibility for human rights. Using a normative juridical method, this paper relies on secondary data comprising primary, secondary, and tertiary legal materials. The analysis employs both statutory and conceptual approaches. The findings indicate that large-scale forest fires, especially those caused by deliberate human activities, violate the right to a good and healthy environment. Consequently, the government is obliged to take strict action against perpetrators of forest fires and ensure recovery efforts for communities affected by these environmental disasters. This reinforces the state's obligation to uphold human rights by safeguarding the environment and addressing the consequences of environmental harm caused by forest fires.